(untitled) (Quest Journal of Management and Social Sciences, 2023)
Background: Online shopping is a pivotal component of electronic commerce, allowing consumers to purchase products or services directly from sellers over the Internet. It typically involves using a web browser to access digital storefronts hosted by retailers. Its significance continues to grow as technology evolves and consumer preferences adapt to the digital age. Objective: The main objective of this study is to examine the effect of price, convenience, and security on the online shopping behaviour of college-level students in Kathmandu. Valley. Design/methodology/Approach: The study employed an analytical research design and targeted college-level students from the different colleges of the Kathmandu Valley involving online shopping. We selected 400 respondents using a convenience sampling technique. Primary data has been collected by adopting a well-structured questionnaire mainly containing a five-point Likert scale. We applied correlation and regression approaches to analyze and interpret the data to obtain the outputs of the study. Findings: The study reveals an association between price, convenience, and security with online shopping behaviour. The result also showed that online shopping behaviour is significantly influenced by two main factors, namely convenience and price. Nevertheless, security is a relatively insignificant determinant of online shopping behaviour. However, gender does not affect all the variables. Conclusion: In summary, for college students, online shopping behaviour is significantly influenced by price and convenience, with security playing a minor role. Online shopping companies should focus on user-friendly website design and stable pricing to attract and retain customers. A well-designed marketing mix aligned with customer expectations is crucial for effective online business. Government support for network infrastructure and online business policies is also essential. Keywords: Online shopping behaviour, price, convenience, security, and students